مية النباتية للزيوت العطرية األساسية ومسحوق األو ارق ألربعة نباتات طبية ُ الس على البالغات ويرقات خنفساء الدقيق المتشابهة Duval confusum Tribolium (Coleoptera: Tenebrionidae) - محفوظ, نوال عبدالسلام; الصغير, بثينة مصطفي (The Libyan Journal of Science, 2021)
Flour beetles Tribolium confusum Duval (Coleoptera: Tenebrionidae) cause a major loss of stored grains and their products. Control of this pest remains weak and relies on traditional insecticides; it requires the use of safe and effective alternatives to synthetic insecticides such as medicinal plant extracts. The purpose of this study is to assess the toxic effects of essential aromatic oils and leaf powder of four medicinal plants: mint Mentha rotundifolia L., sweet basil Ocimum basilicum L., clove Syzygium aromaticum L., eucalyptus Eucalyptus globulus Labill on adult insects and larvae of T. confusum. Results showed toxic effect of essential aromatic oils and leaf powder on adult’s death and larvae of flour beetles T. confusum in a period of 72 hours a significant difference at 0.001 level. Data indicated no significant differences between the two plant formulas of essential aromatic oils and leaf powder, and between three concentrations diluted with ethyl alcohol namely, 10%, 20%, 30% (v/v) mixed with 5g flour. Sweet basil revealed a high toxic effect at 0.001, 0.05 significant difference levels on T. confusum adults and larvae. Clove, mint and eucalyptus treatments revealed significant difference levels on Flour beetle adults and larvae. In contrast, mint did not show any toxic significant difference effect on T. confusum adults and larval stages. Results also displayed an interaction of treatments x oils a high significant difference level at 0.001. The interaction of treatment x adults and larval stages, and treatment x adults and larval stages x plant condition showed significant difference levels at 0.05. Lab results demonstrated phytotoxic and repellent effect of medicinal plants essential aromatic oils and leaf powders that have an effective and safe Integrated Pest Management strategy of stored grains pests and their products.